Clustering approach on layout redesign to optimize container handling process - Sugiyono, Andre (Penerbit Universiti Kebangsaan Malaysia, 2020)
Container Terminal of Semarang is a service provider for export and import container handling process. It represents one of the divisions of PT (Persero) Port of Indonesia III Branch TanjungEmas Semarang. As an anticipatory step to growth of containership capacity in Port of Indonesia III Semarang, the company need to improve the quality of container handling service and to reach a higher level of productivity. One of the ways to achieve these goals is to focus on layout planning and management that can potentially be beneficial to all factors involved such as space exploitation, process efficiency etc. The layout planning of a container terminal can significantly benefit from using Group Technology approach in which containers can be grouped into families of containers and transported between cells(block locations in the yard).With this type of layout, the company has many advantages like flexibility on production process to address high variability in the system. As a result, it can give alternative arrangement of container in the yards. We observed that based on Bond Energy Algorithm (BEA) method, container travel distance can be reduced to 188.06 metres/ month, which is approximately 9 % saving of distances travelled by each container. Moreover, using Group Technology approach can provide a higher flexibility to cope with fluctuations in process.